Instruments Assessing Cognitive Impairment in Survivors of Critical Illness and Reporting of Race Norms: A Systematic Review. (22nd December 2022) - Raman, Rameela; DesAutels, Spencer J.; Lauck, Alana M.; Scher, Alexa M.; Walden, Rachel L.; Kiehl, Amy L.; Collar, Erin M.; Ely, E. Wesley; Pandharipande, Pratik P.; Jackson, James C.
Abstract : OBJECTIVE: To conduct a systematic review to summarize cognitive instruments being used in long-term outcome studies of survivors of adult critical illness, as well as evaluate whether these measures are reported as using patient demographic norms, specifically race norms. DATA SOURCES: A comprehensive search was conducted in PubMed (National Center for Biotechnology Information), Excerpta Medica dataBASE (Ovid), Psychological Information Database (ProQuest), and Web of Science (Clarivate) for English language studies published since 2002. STUDY SELECTION: Studies were eligible if the population included adult ICU survivors assessed for postdischarge cognitive outcomes. DATA EXTRACTION: Two independent reviewers screened abstracts, examined full text, and extracted data from all eligible articles. DATA SYNTHESIS: A total of 98 articles (55 unique cohorts: 22 general ICU, 14 Acute respiratory distress syndrome/Acute respiratory failure/Sepsis, 19 COVID-19 and other subpopulations) were eligible for data extraction and synthesis. Among general ICU survivors, the majority of studies ( n = 15, 68%) assessed cognition using multiple instruments, of which the most common was the Mini-Mental State Examination. Only nine of the 22 studies (41%) explicitly reported using patient demographic norms for scoring neuropsychological cognitive tests. Of the nine, all reported using age as a norming characteristic, education was reported in eight (89%), sex/gender was reported in five (55%), and race/ethnicity was reported in three (33%). Among Acute respiratory distress syndrome/Acute respiratory failure/Sepsis survivors, norming characteristics were reported in only four (28%) of the 14 studies, of which all reported using age and none reported using race/ethnicity. CONCLUSIONS: Less than half of the studies measuring cognitive outcomes in ICU survivors reported the use of norming characteristics. There is substantial heterogeneity in how studies reported the use of cognitive instruments, and hence, the prevalence of the use of patient norms may be underestimated. These findings are important in the development of appropriate standards for use and reporting of neuropsychological tests among ICU survivors.